Angular Distributions of Relativistic Electrons Under Channeling in Half-Wave Crystals and Corresponding Radiation; Charged and Neutral Particles Channeling Phenomena - Takabayashi Yu. Yuichi; Багров В. Г. Владислав Гаврилович; Pivovarov Yu. L. Yuriy Leonidovich; Bogdanov O. V. Oleg Viktorovich; Tukhfatullin T. A. Timur Ahatovich (2014, 2014)
Title screen